2008
DOI: 10.2116/analsci.24.677
|View full text |Cite
|
Sign up to set email alerts
|

Release Mechanism from a Microsphere of a Silkworm Chitin Derivative Studied by Single Microparticle Injection and Absorption Microspectroscopy

Abstract: The release process of phenol blue from a dibutyrylchitin microsphere, prepared with chitin from a silkworm, into an aqueous solution was kinetically analyzed by single microparticle injection/manipulation and absorption microspectroscopy. The distribution ratio and the release rate of phenol blue in the single microsphere/water system were significantly influenced by the pH of the solution. These results are discussed in terms of the protonation of phenol blue and dibutyrylchitin, and the pore and surface dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[14][15][16] In those reports, as the mass transfer rate in the microparticle/solution system was assumed to be limited by the intraparticle diffusion, the intraparticle diffusion coefficient (Dp) was estimated. When the supposed Dp value was independent of the microparticle diameter (d), the intraparticle diffusion was analyzed in detail on the basis of the pore and surface diffusion model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] In those reports, as the mass transfer rate in the microparticle/solution system was assumed to be limited by the intraparticle diffusion, the intraparticle diffusion coefficient (Dp) was estimated. When the supposed Dp value was independent of the microparticle diameter (d), the intraparticle diffusion was analyzed in detail on the basis of the pore and surface diffusion model.…”
Section: Introductionmentioning
confidence: 99%
“…When the supposed Dp value was independent of the microparticle diameter (d), the intraparticle diffusion was analyzed in detail on the basis of the pore and surface diffusion model. [14][15][16] For mass transfer of perylene as a water-insoluble organic compound in the presence of Triton X-100 (nonionic surfactant) in an ODS-silica gel/water system, however, the supposed Dp value depended on d, indicating that the mass transfer rate cannot be analyzed as the intraparticle diffusion. 17 From the d dependence of mass transfer rate, we concluded that the rate-determining step was the micelle-mediated solubilization of the dye at the microparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,17 As the rate-determining step of the perylene release rate is assumed to be the intraparticle diffusion, the intraparticle diffusion coefficient of perylene or Triton X-100 (Do) was determined from A(t). The t dependence of the radial concentration profile in the microparticle (Cp(r,t)) is given by the spherical diffusion equation: ∂Cp(r,t)/∂t = Do{∂ 2 Cp(r,t)/∂r 2 + (2/r)∂Cp(r,t)/∂r}, where r is the radially directed spatial coordinate.…”
Section: Resultsmentioning
confidence: 99%
“…3,8,10,17 In these systems, the rate-determining step of the sorption or release was the intraparticle diffusion, and the intraparticle diffusion could be discussed on the basis of the pore and surface diffusion model. In the present paper, we report the release of perylene as a water-insoluble organic compound from single ODS-silica gel microparticles into the water phase in the presence of polyoxyethylene (10) octylphenyl ether (Triton X-100).…”
Section: Introductionmentioning
confidence: 99%